Analysis of Criminal Punishment of Perpetrators of The Criminal Act of Theft with Aggrevaction from The Perspective of Legal Certainty (Study of Decision Number 126/Pid.B/2024/PN Pml) - Marpaung, Marzuki Joshua; Laksana, Andri Winjaya (Jurnal Hukum Khaira Ummah, 2025)
This study aims to analyze the legal aspects of the crime of aggravated theft in the context of social justice, focusing on Case Number 47/Pid.B/2022/PN Lbo. This study examines the application of criminal sanctions to the perpetrator and considers the judge's perspective in issuing the verdict. The research problem formulation covers two main aspects: first, how criminal sanctions are applied in this case, and second, how the judge's considerations reflect the values of social justice. This study uses a descriptive analysis method to explore the legal aspects of the crime of aggravated theft, focusing on Case Number 47/Pid.B/2022/PN Lbo. The research findings demonstrate the importance of a social justice-based approach to law enforcement, which focuses not only on punishment, but also on rehabilitation and crime prevention, to create a fairer and more effective justice system.